Wearable Antenna Mikrostrip Untuk Aplikasi Teknologi 5g - Pradiya, Rizan; Nugroho, Bambang Setia; Aziz, Arif Abdul (eProceedings of Engineering, 2024)
In daily life, there are still many challenges related to the long-range signal transmission, such as Wi-Fi and Bluetooth, which have a limited range of around 10 meters. To address this issue, we have developed a "Wearable Microstrip Antenna for 5G Technology Applications" using the inset-feed method at a frequency of 3.5 GHz to align with the 5G technology standards. This usable microstrip antenna has drawbacks, such as low gain and surface waves that can affect radiation patterns. Therefore, we pay attention to the Specific Absorption Rate (SAR) values that are safe for the human body (1.6 W/kg) and employ a unidirectional radiation pattern to ensure safety when used on the human body. The primary objective of developing this antenna is to simplify human daily life with a smaller, lighter size that can be attached to clothing. Testing was conducted on the wearable antenna with an operating frequency of 3.5 GHz, ensuring that the SAR values remained below the safe limit of ≤1.6 W/kg. The test results revealed a VSWR value of 1.4815, a return loss of -11.332 dB, a bandwidth exceeding 351.4 MHz, and a gain of 3.098 dB. Keywords: Wearable, Antena, Mikrostrip, 5G